Pendekatan Produksi Bersih Dalam Industri Pengolahan Bakso Ikan Di Desa Harapan Kecamatan Pemangkat - Abdurrahman; Anggi; Hairulaila; Nadia; Nazri; Merdekawati, Dewi (Jurnal Perikanan dan Kelautan, 2025)
The fish ball processing industry has significant economic potential, but it also has environmental impacts due to the solid and liquid waste it produces. This study aims to evaluate the potential for implementing a cleaner production approach in the household-scale meatball processing industry in Harapan Village to improve sustainability and competitiveness for the local industry. The method used in data collection in this study was through observation and interviews with household-scale fish ball businesses. Based on the research, the fish ball processing industry in Harapan Village produces two types of waste: liquid waste consisting of fish washing water and fish meat washing water, and solid waste in the form of fish bones and scales. The cleaner production approach applies 5 principles: elimination (prevention), reduce (reduction), reuse (reuse), recycle (recycling), and recovery (recovery of valuable materials) which have not been implemented by business actors. Thus, the household-scale fish ball processing industry in Harapan Village still requires significant improvements in cleaner production.